Efficiency of different clay minerals modified with a cationic surfactant in the adsorption of pesticides: Influence of clay type and pesticide hydrophobicity - Sanchez-Martin, M.J.; Rodriguez-Cruz, M.S.; Andrades, M.S.; Sanchez-Camazano, M.
In the present work we studied the efficiency of a series of clay minerals (montmorillonite, illite, muscovite, sepiolite and palygorskite)modified with the cationic surfactant octadecyltrimetylammonium bromide (ODTMA)in the adsorption of the pesticides penconazole, linuron, alachlor, atrazine and metalaxyl. A study was also carried out on the effect of the structure (expansible and non-expansible layered, and non-layered), the surface area and charge density of the clay minerals, and the hydrophobicity of the pesticides (Kow)on the adsorption process. Adsorption-desorption isotherms of the pesticides by clay minerals were obtained and the constants of the Freundlich model (Kf and Kfd)(natural clays)and of the linear model (K and Kdes)(ODTMA-clays)were determined. Correlation coefficient values (r2)found between K and Kdes, and organic matter (OM)content of ODTMA-clays indicate a more effective partitioning of the pesticides in the organic phase of ODTMA after desorption. Furthermore the positive significant correlation found between the Kdesom values and the charge density of different ODTMA-clays indicates that a higher density of ODTMA in the clay gives rise to the formation of an organic phase more effective for the partition of the pesticides. This correlation explained that the highest Kdesom value obtained was for kaolinite and the lowest Kdesom value was for montmorillonite in the adsorption of all pesticides by the different organo clays. Simple correlations between adsorption constants and Kow values, and multiple correlations between these constants and clay OM contents and Kow values were also calculated. The results obtained indicate the interest of ODTMA-clays in the adsorption of hydrophobic pesticides. Non-expandible layered and fibrous clay minerals may also be of interest as adsorbents derived from their density charge, and these minerals, when modified with ODTMA, and used in appropriate amounts, higher than that of montmorillonite, or when present in soils with high clay contents, even in the absence of montmorillonite, may be good adsorbents for hydrophobic pesticides. According to the results of the study, ODTMA-clays and ODTMA-soils could be used as barriers to prevent the mobility of certain hydrophobic pesticides from a point source of pollution
Keywords: LAYERED ORGANOCLAYS; NON-LAYERED ORGANOCLAYS; ADSORPTION; DESORPTION; PESTICIDES; POINT-SOURCE POLLUTION